Evidence for a rotation in asthenospheric flow in northwest Canada: insights from shear wave splitting - Bolton, Andrew R., author; Schutt, Derek L., advisor; Aster, Richard C., committee member; Breidt, F. Jay, committee member (Colorado State University. Libraries, 2021)
The Mackenzie Mountains (MM) of northwest Canada are an actively uplifting, seismogenic salient of the northern Canadian Cordillera that lie 750 km NE of the nearest plate boundary. We present new shear wave splitting measurements for the region from a linear array which transects the region to characterize upper mantle anisotropy. A gradual rotation in anisotropy occurs across the Canadian Cordillera, with stations nearest to the craton yielding fast axis orientations that are subparallel to North America absolute plate motion (~230°). Moving SW from the craton, across the MM and towards the plate boundary, fast-axis orientations rotate to become aligned with major lithospheric fabrics (NW-SE). Previous work has shown that the Cordilleran lithosphere is thin (~50 km) in this region. We therefore interpret these results to primarily reflect sublithospheric flow. Three subduction-transpressional related hypotheses for flow are presented, where our preferred hypotheses invokes depth-dependent, subduction-induced flow.
Keywords: northwest Canada; shear wave splitting; seismology; mantle anisotropy